An Insular Reliquary from Melhus: The Significance of Insular Ecclesiastical Material in Early Viking-Age Norway. Issue 1 (2nd January 2018) - Heen-Pettersen, Aina; Murray, Griffin
Abstract : THIS PAPER presents and discusses a unique insular reliquary shrine discovered in an early 9th-century woman's grave at Melhus, central Norway, over a century ago. In addition to a detailed re-evaluation of the shrine and its use in its original ecclesiastical context, the paper also proposes an alternative interpretation as to how the local pagan population may have conceptualised this Christian object after it arrived in Norse hands. While most of the insular ecclesiastical items in Scandinavia were broken up and transformed into personal ornaments, the Melhus shrine was kept complete, suggesting it was considered to be of special value. It is argued here that this status should be seen in association with the shrine's involvement in local narratives and ritual aspects connected with the earliest voyages across the North Sea. The woman with whom the reliquary was buried may have played a central role in these rituals.